Risk factors for deep venous thrombosis of lower limbs in postoperative neurosurgical patients - Li, Qiang (Pak J Med Sci, 2016)
OBJECTIVES: To detect the risk factors for deep venous thrombosis (DVT) in patients after neurosurgery. METHODS: Three hundred and seventy-six patients treated in the department of neurosurgery of our hospital from February 2013 to November 2015 were reviewed retrospectively. The clinical data including age, gender, hospital stay, operation time, occupation type, hypertension, coronary heart disease, diabetes, smoking status, drinking status, postoperative exercises, malignant tumor, and postoperative hormone or dehydrating agent were collected. RESULTS: In this study, 52 patients were included in the DVT group and 295 patients in the Non-DVT group. There was significant difference in age, hypertension, occupation type, malignant tumors, operation time, smoking status, and postoperative exercises between the two groups (p<0.05). However, there was no significant difference in gender, drinking status, coronary heart disease, diabetes, hospital stay, and postoperative hormone or dehydrating agent (p>0.05). In multivariate analysis, age, malignant tumor, hypertension were independent risk factors, while physical labour and postoperative exercises were protective factor for DVT. CONCLUSION: The postoperative patients with older age, malignant tumor or hypertension should be paid high attention to prevent DVT, and postoperative exercises should be selected as precautionary measures.